Flaxseed and mulberry extract improve trabecular bone quality in estrogen-deficient rats - Jacques, Larissa Sampaio; Pereira, Jéssica Petrine Castro; Santos, Beatriz Menegate; Barrioni, Breno Rocha; Del Bianco Borges, Bruno (Climacteric : the journal of the International Menopause Society, 2025)
Many hormones, including estrogens, modulate bone metabolism, which plays a crucial role in maintaining bone health. Estrogen depletion, as occurs in menopause, leads to increased bone resorption and decreased formation, resulting in osteopenia/osteoporosis. This study investigates the effects of flaxseed ( ) and mulberry ( L.) extracts, known for their phenolic compounds and antioxidant properties, against estrogen deficiency-induced bone loss in female Wistar rats. These extracts were administered to ovariectomized rats for 60 days. High-performance liquid chromatography analysis revealed the presence of some phenolic compounds in the extracts, including trigonelline, gallic acid, theobromine, chlorogenic acid, syringic acid and -coumaric acid. The extracts improved bone microstructure with higher trabecular bone, bone mineral density, calcium, phosphorus and magnesium levels, and lower porosity and intertrabecular space in bone tissue. Furthermore, plasma alkaline phosphatase activity was elevated in extract-treated animals, indicating enhanced bone tissue formation. Although serum carboxy-terminal fragment levels showed no significant change, the data suggest that flaxseed and mulberry extracts may protect against trabecular bone loss and support bone formation in estrogen-deficient conditions. These results suggest that supplementing these natural extracts holds promise in preventing or alleviating the signs and symptoms associated with estrogenic deficiency.